122 UNUSUAL CASE OF SEROTONIN SYNDROME WITH THERAPEUTIC DOSE OF PAROXETINE. (1st January 2006) - Godkar, D.; Paruchuri, P.; Anandacoomarswamy, D.; Sheth, K.; Niranjan, S.
Abstract : Background: Paroxetine (Paxil) is a selective serotonin reuptake inhibitor (SSRI), FDA approved for the treatment of panic disorder, depression, social anxiety disorder, generalized anxiety disorder, posttraumatic stress disorder, OCD, and premenstrual dysphoric disorder. Its efficacy is linked to potentiation of serotoninergic activity in the central nervous system resulting from inhibition of neuronal reuptake of serotonin (5-hydroxytryptamine, 5-HT). A dreaded iatrogenic complication of administering Paxil and other SSRIs is the serotonin syndrome. It has normally been reported to have occurred with concomitant administration of MAOIs and SSRIs or in significant overdose of SSRI. It has rarely been reported with therapeutic doses of paroxetine. Only one other case was found in our research. Case Report: We present a case of an 80-year-old Russian female who presented with altered mental status, myoclonus, and rhabdomyolysis. Her medical history was significant for major depression treated with paroxetine for thr last 6 months. After ruling out infectious, metabolic, cerebrovascular, and cardiac causes for her change in mentation, we diagnosed her with serotonin syndrome due to the administration of paroxetine, albeit at therapeutic doses. After immediately discontinuing the offending drug, the patient was aggressively hydrated with fluids and treated with an antiserotoninergic agent, cyprohepatidine. She responded to the cyproheptadine and fully recovered by day 3 of admission. Discussion: The serotonin syndrome is an iatrogenic complication of proserotoninergic drugs comprising of at least three signs and symptoms reflecting mental status changes, autonomic instability, and neuromuscular abnormalities. As the exposure to proserotoninergic drugs is increasing, so is the incidence of the serotonin syndrome. Our research shows that the syndrome has mainly occurred in conjunction with overdoses, drug interactions such as concomintant use of MAOIs or neuroleptics, and in pediatric populations. However, we report a case where the syndrome occurred in a patient who was taking paroxetine routinely at therapeutic doses. Conclusion: It is important to suspect this potentially lethal and possibly reversible cause in any patient that presents acutely with mental status changes and is known to be on proserotoninergic drugs regardless of duration and dosage. Early suspicion would help the patient's prognosis while also preempting numerous diagnostic tests and possibly harmful treatments. Although the reported incidence of serotonin syndrome is 0.4/1, 000, its actual incidence might be underestimated due to lack of clinical suspicion and diagnosis.